Language Peculiarities of One of the Great Russian Translations from Polish Dating to the End of the 17th Century (On the Question of the Influence of Polish on the Literary Language of Moscow Russia in the 17th Century) - Целунова, Е. А. (Kalbotyra, 1987)
The present paper is devoted to linguistic analysis of the Psalter of 1683 translated from the Polish language by Avramy Firsov. The translator himself defined the language of the Psalter as being “simple slavonic”. The scrutiny of the Psalter language shows that Firsov considered it to be bookish, as he did not make use of specific Russisms as opposed to Church Slavonic. Normative Russisms for the Psalter are only those prompted to Firsov by the Polish texts.